2013
DOI: 10.1007/s00216-013-7463-3
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-linked immunosorbent assay in analysis of deoxynivalenol: investigation of the impact of sample matrix on results accuracy

Abstract: Enzyme-linked immunosorbent assay (ELISA) represents a bioanalytical strategy frequently used for rapid screening of mycotoxin deoxynivalenol (DON) in cereals and derived products. Due to a considerable affinity of some anti-DON antibodies to structurally similar DON metabolites, such as DON-3-glucoside (DON-3-Glc) and 3-acetyl-DON (3-ADON), a significant overestimation of DON concentrations may occur. A validation study of six commercial DON-dedicated ELISA kits, namely Ridascreen DON, Ridascreen FAST, DON, D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The results obtained in this study are doubtful for several reasons. First of all, AgraQuant ® was found to be a kit that overestimates the DON content compared to LC-MS/MS results [ 23 – 25 ]. Two comprehensive studies performed on four commercially available DON ELISA kits revealed that DON overestimation is caused by both cross-reactivity with structurally related compounds and by matrix effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The results obtained in this study are doubtful for several reasons. First of all, AgraQuant ® was found to be a kit that overestimates the DON content compared to LC-MS/MS results [ 23 – 25 ]. Two comprehensive studies performed on four commercially available DON ELISA kits revealed that DON overestimation is caused by both cross-reactivity with structurally related compounds and by matrix effects.…”
Section: Resultsmentioning
confidence: 99%
“…Two comprehensive studies performed on four commercially available DON ELISA kits revealed that DON overestimation is caused by both cross-reactivity with structurally related compounds and by matrix effects. Although the kit manufacturer stated that the cross-reactivity with 3ADON was >100 %, two studies reported it to be more than 300 % based on the solvent standard [ 24 , 25 ]. Cross-reactivity with D3G was found to be 113 % in the latter study [ 25 ], while Tran and Smith [ 15 ] based their calculations on a mere 4.8 %, as specified by the manufacturer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Паралельно з цим, в останні роки збільшилась увага до більш простих у використанні та високочутливих імуноферментних методів аналізу (ELISA). В літературі є повідомлення про використання ELISA для аналізу дезоксиніваленолу [20,21], афлатоксину B1 [21,22], зераленону та охратоксину [21], одночасного визначення афлатоксину В1 і афлатоксину М1 [23].…”
Section: вступunclassified